Copper(I)-catalyzed sulfonylative Suzuki-Miyaura cross-coupling - Willis, M; Chen, Y (Royal Society of Chemistry, 2017)
Using a simple copper(I) catalyst has allowed a high yielding sulfonylative-Suzuki-Miyaura cross-coupling to be developed. The process provides a single step route to diaryl sulfones from the direct combination of aryl boronic acids, sulfur dioxide and aryl iodides, and represents the first sulfonylative variant of a classic cross-coupling reaction. Sulfur dioxide is delivered from the surrogate reagent, DABSO. Variation of the reaction conditions allowed interruption of the sulfonylative-Suzuki coupling, resulting in formation of a presumed Cu-sulfinate intermediate. These sufinates could be trapped with electrophiles to access to arylalkyl sulfones, β-hydroxyl sulfones, sulfonamides and sulfonyl fluorides.